The relationship between habitual physical activity status and executive function in individuals with Alzheimer's disease: a longitudinal, cross-lagged panel analysis. Issue 2 (3rd March 2016) - Farina, Nicolas; Tabet, Naji; Rusted, Jennifer
Abstract: To determine whether habitual physical activity status specifically influences executive function change in Alzheimer's disease (AD) over 1 year. In this longitudinal cohort study, 45 participants with AD were recruited and provided follow-up data approximately 1 year later. Executive function measures (map search task, digit symbol substitution task, controlled oral word association task, verbal fluency task) and habitual physical activity measures (Physical Activity Scale for the Elderly (PASE) and handgrip strength) were taken at baseline and follow-up. Individual composites were subsequently created. Additional demographic, lifestyle, and neuropsychiatric measures were also taken. In a structural equation model (χ 2 (26) = 9.84, p = .998, comparative fit index = 1.00, root mean square error of approximation = .00), a significant association was found between habitual physical activity and executive function change (β = .27, p = .04). In a cross-lagged panel analysis, a significant path was found between the PASE score and executive change (β = .22, p = .01). As higher habitual physical activity levels were associated with reduced executive function change, the promotion of low-intensity habitual physical activities in individuals with a diagnosis of AD may be warranted. Further research is needed, however, to explore the impact of habitual physical activity on the trajectory of change across cognitive domains, and how this relates to the progression of the underlying pathology associated with this disease.